Los osos scouts Berenstain salvan a rascaepaldas - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012. (New York : Scholastic, 1996)
Los osos scouts Berenstain llegan al rescate! El alcalde quiere cortar el arbol mas famoso del Pais de los Osos.
Translation of: The Berenstain Bear Scouts save that backscratcher.
"A Little Apple paperback."
Accelerated Reader AR
Keywords: Diaz Benzo, Antonio -- Literatura juvenil; Bears -- Fiction; Osos -- Literatura juvenil; Spanish language materials; Fiction